(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2019)
Among sub-Saharan migrants who enter irregularly in Europe, there is a particularly vulnerable group: the one formed by single mothers with dependent children and pregnant women. This article addresses the characteristics of this peculiar migration and the deficiencies of the system to achieve effective protection.